An Obituary for Götz Hillig (15 February 1938 – 6 June 2019), the Important Makarenko Researcher - Waterkamp, Dietmar (International Dialogues on Education Journal, 2019)
An Obituary for Götz Hillig (15 February 1938 – 6 June 2019), the Important Makarenko Researcher